A Comparative Analysis of Korean-English Phonological Structures and Processes for Pronunciation Pedagogy in Interpretation Training - Cho, Junmo; Park, Hae-Kyeong (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2006)
AbstractThis paper discusses the rationale for providing pronunciation training in B language to students of interpretation working into B. It also provides a thorough comparative analysis of Korean-English phonological structures and processes followed by pedagogical suggestions for instructors of interpretation. This study concludes that with the proper knowledge on the contrastive analyses of phonetic/phonological structures and processes and with proper instruction and practice, Korean students of interpretation will acquire better speech delivery and interpretation quality into English.